2021
DOI: 10.1016/j.tust.2020.103608
|View full text |Cite
|
Sign up to set email alerts
|

The effect of technical installations on evacuation performance in urban road tunnel fires

Abstract: Tunnels are separated from the ground by structural linings, and are enclosed and unfamiliar for occupants. In tunnel fires, occupants are faced with a dangerous environment and they need to evacuate. Conveying and obtaining information about the evacuation is the key issue for evacuees. Since tunnels typically have low lighting and little connection outside the tunnel, technical installations are the only approach to deliver information to occupants in order to guide their fast and safe evacuation. This is pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The temperature range of concern in this paper are the ambient temperatures experienced during a normal service life [33], rather than (for example) the extreme temperatures related to fire [34,35]. As noted in the outline, the load cycles considered here are daily variations, not the higher frequency cycles due to traffic crossing.…”
Section: The Cyclic Temperature and Cyclic Load Scenariosmentioning
confidence: 99%
“…The temperature range of concern in this paper are the ambient temperatures experienced during a normal service life [33], rather than (for example) the extreme temperatures related to fire [34,35]. As noted in the outline, the load cycles considered here are daily variations, not the higher frequency cycles due to traffic crossing.…”
Section: The Cyclic Temperature and Cyclic Load Scenariosmentioning
confidence: 99%
“…The speed/acceleration of evacuees is jointly affected by the above three factors and is determined by equation (7). During the evacuation, the force effect of the latter two items of equation ( 7) is great, which makes it difficult for evacuees to achieve a high travel speed at bottlenecks.…”
Section: Interaction Force F Ij Of Granular I With Other Granularsmentioning
confidence: 99%
“…Approximately 4.2% of passengers were obstructed when passing through gate-type gates; however, 17.9% of passengers were obstructed when passing through three-bar gates. Zhang et al 7 studied technical installations (alarms, information signs and lighting) on people's evacuation performance through field experiments, questionnaires and interviews and found that good visual conditions are the key to evacuation efficiency and can effectively reduce casualties.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (13) explored the characterization of ceiling smoke temperature profile in a ventilation tunnel. Zhang et al (14) investigated the effect of technical installations on evacuation performance in urban road tunnel fires. However, the past studies mainly focused on the danger of a fire accident in a tunnel.…”
Section: Biogas Detection System In Shield Tbmmentioning
confidence: 99%